Accelerated high frequency rTMS induces time-dependent dopaminergic alterations: a DaTSCAN brain imaging study in healthy beagle dogs - Xu, Yangfeng; Peremans, Kathelijne; Salden, Sofie; Audenaert, Kurt; Dobbeleir, Andre; Van Eeckhaut, Ann; De Bundel, Dimitri; Saunders, Jimmy H.; Baeken, Chris (Frontiers in Veterinary Science, 2023)
Aim: The neurobiological effects of repetitive transcranial magnetic stimulation are believed to run in part through the dopaminergic system. Accelerated high frequency rTMS (aHF-rTMS), a new form of stimuli delivery, is currently being tested for its usefulness in treating human and canine mental disorders. However, the short- and long-term neurobiological effects are still unclear, including the effects on the dopaminergic system. In aHF-rTMS, multiple sessions are delivered within one day instead of one session per day, not only to accelerate the time to response but also to increase clinical efficacy. To gain more insight into the neurobiology of aHF-rTMS, we investigated whether applying five sessions in one day has direct and/or delayed effects on the dopamine transporter (DAT), and on dopamine metabolites of cerebrospinal fluid (CSF) in beagles. Materials and methods: Thirteen beagles were randomly divided into two groups: five active stimulation sessions (n = 9), and 5 sham stimulation sessions (n = 4). Using DaTSCAN, DAT binding indices (BI) were obtained at baseline, after one day, one month, and three months post stimulation. CSF samples were collected after each scan. Results: Active aHF-rTMS significantly reduced striatal DAT BI one day post-active stimulation session (p < 0.01), and the effect lasted to one month (p < 0.01). No significant DAT BI change was found in sham group. No significant changes in dopamine metabolites of CSF were found. Conclusion: Although no significant effects on CSF dopamine metabolites were observed, five sessions of active aHF-rTMS significantly decreased striatal DAT BI after one day and up to one month post stimulation, indicating immediate and delayed effects on the brain dopaminergic system. Our findings in healthy beagles further substantiate the assumption that (a)HF-rTMS affects the brain dopaminergic system and it may pave the way to apply (a)HF-rTMS treatment in behaviorally disturbed dogs.